2023
DOI: 10.3389/fpubh.2023.1099260
|View full text |Cite
|
Sign up to set email alerts
|

Association between specific social activities and depressive symptoms among older adults: A study of urban-rural differences in China

Abstract: BackgroundEngaging in social activities can help older persons with their depressed symptoms. Few studies, however, have looked into the connection between social interactions and depressed symptoms in Chinese older persons. The aim of this study was to investigate differences in older Chinese individuals' social activity involvement and depressive symptoms across urban and rural settings.MethodsA cross-sectional investigation using information from the 2018 China Health and Retirement Longitudinal Study (CHAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…However, this relationship was only discovered in the full sample and among older adults residing in urban areas. Our findings support those of earlier studies showing that physical activity levels are significantly associated with depressive symptoms among urban older adults but not rural older adults [35]. In addition, a study by Mumba et al [36] found that the correlation between physical activity and depressive symptoms varied among culturally diverse ethnicities of older adults residing in the United States.…”
Section: Discussionsupporting
confidence: 91%
“…However, this relationship was only discovered in the full sample and among older adults residing in urban areas. Our findings support those of earlier studies showing that physical activity levels are significantly associated with depressive symptoms among urban older adults but not rural older adults [35]. In addition, a study by Mumba et al [36] found that the correlation between physical activity and depressive symptoms varied among culturally diverse ethnicities of older adults residing in the United States.…”
Section: Discussionsupporting
confidence: 91%
“…42 Third, the rural elderly have as a priority the care-taking of left behind grandchildren when their offspring move to large cities to seek employment. In contrast, urban elderly are usually better educated, have a fixed income and persist in maintaining their social roles within their family and society, 28 enabling them to be more participative in social activities.…”
Section: Discussionmentioning
confidence: 99%
“…This study explores and evaluates the relationship between engagement in social activities and the mitigation of depressive symptoms among older individuals within the context of urban and rural areas in China. Specifically, this study examines differences in social activity engagement between rural and urban elderly populations 28,29 and type of social activity engagement by elderly persons and depressive symptoms, and variations in engagement in social activities and depression among rural and elderly populations to address an identified gap in the literature 30 considering the wide distribution of the population in China.…”
Section: Introductionmentioning
confidence: 99%